Скважинные амортизаторы - Островский, И.Р.; Сирик, В.Ф.; Луцик, А.С.; Полушко, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The drill hole shock absorber consists cylinder spring to reduce amplitude of vertical and
torsion vibrations. The using shock absorber to rise drill bit resource to 20-30 % within drill productivity increasing on 15-25 %.